2021
DOI: 10.46338/ijetae0821_09
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Online Learning During theCovid-19 Pandemic (Case Study: Private University in Jakarta)

Abstract: -The virus Covid-19 has caused enough trouble for the whole world for nearly a year, ever since it first emerged in Wuhan, China, in December 2019. All areas of life are affected in a way or more, especially the education sector. Learning process shifting to be online at home, and it is now commonly referred to as online learning. Despite the now regulated way of learning, debates regarding the effectiveness of online learning are widely circulated. Thus, the purpose of this study is to investigate the effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Meanwhile, other studies found that online learning during the COVID-19 pandemic is equally effective as the one conducted offline (Jones et al, 2020). Furthermore, online learning is appropriate to implement during the COVID-19 pandemic (Allo, 2020;Kalman et al, 2020) and positively impacts during the COVID-19 pandemic (Hendryka et al, 2021). Learning online is easy, cheap, and can be implemented (Agarwal & Kaushik, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, other studies found that online learning during the COVID-19 pandemic is equally effective as the one conducted offline (Jones et al, 2020). Furthermore, online learning is appropriate to implement during the COVID-19 pandemic (Allo, 2020;Kalman et al, 2020) and positively impacts during the COVID-19 pandemic (Hendryka et al, 2021). Learning online is easy, cheap, and can be implemented (Agarwal & Kaushik, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…De récents résultats remettent en question aussi les compétences développées lors de la pandémie, alors que les taux de réussite, notamment en sciences infirmières, sont alarmants (Boily et Paquette-Comeau, 2022). Pourtant, de nombreuses études suggèrent que les personnes apprenantes en enseignement supérieur réussissent mieux en modes FAD ou hybride (Hendryka et al, 2021;Sri et al, 2022). Il est ici difficile de distinguer la cause de ces écarts, à savoir le vécu scolaire pendant la période pandémique, ou les changements dans les méthodes d'enseignement, et il est probablement encore un peu tôt pour constater les effets de cette transition.…”
Section: Discussionunclassified
“…This way of learning strongly influences their learning achievement, self-efficacy, and learning motivation. Sources of effects come from how learning materials are delivered, how classes are held, and the educators themselves (Hendryka et al, 2021). The University provides a flexible digital pathway through course materials and resources, conducts online lectures, accepts student work submissions, interacts with students, and guides each student to meet their learning goals (Shishakly & Sabah, 2021).…”
Section: What Have Effects Of Online Learning During the Covid-19 Pan...mentioning
confidence: 99%
“…Many institutions have used different social media platforms for knowledge dissemination (Dutta & Dutta, 2020). This learning method is supported by several applications such as Zoom, Google Classroom, and Microsoft Teams that allow lecturers and students to interact together even though everyone is at home (Hendryka et al, 2021;Sharma, 2020;Silalahi, 2021). The Google Classroom web service is ideal for use in lectures.…”
Section: What Have Effects Of Online Learning During the Covid-19 Pan...mentioning
confidence: 99%
See 1 more Smart Citation